Kedudukan Premisse Akta Dalam Undang-Undang Jabatan Notaris - Yasa, Gde Kosika; Putra, Made Aditya Pramana (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 02 (2022)DO - 10.24843/AC.2022.v07.i02.p9, 2022)
The purpose of this article is to find out and analyze the premise arrangement of the deed in the Notary Position Act and the notary's responsibility for the premise of the notary deed. This research examines empty norms with normative research methods, statutory approaches and conceptual approaches. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study indicate that the position of the premise on the deed has a facultative nature, that is, not all notary deeds are listed on the premise of the deed, but in general the premise is listed on the complicated deed. The premise in an authentic deed has a central role where it contains important information before entering the body (content) of the deed being made. The responsibility related to the premise of the deed is the responsibility of the appearers because from the understanding of the premise above that all parts of the premise are the information given by the appearers. In this case, the role of the notary is passive or only records the notarial deed from the agreement of the appearers who come to the notary which aims to guarantee the rights and obligations of the appearers. So that in the future a problem arises where the error is in the statements of the appearers or in the material truth is the responsibility of the appearers who submit it.